Visual processing in expert drivers: What makes expert drivers expert?. (May 2018) - Pammer, Kristen; Blink, Caroline
Highlights: Core underlying cognitions/perceptions differ for expert drivers. Demonstrated using non-driving tasks such as search, object tracking, task maintenance. Experts responded like young participants in these core processing tasks. Experts differed from age-matched control drivers. Expert driving may facilitate maintenance of high levels of visuo/cognitive processing. Abstract: The aim of this study is to measure some visuo-cognitive mechanisms of expert drivers, and compare them to experienced, competent and novice drivers as a way of gaining an understanding of how expert drivers might differ from non-expert drivers. Instead of driving-related stimuli, we used non-driving visual and cognitive tasks that theoretically should underlie good driving skills, such as scanning the environment for targets, tracking multiple objects, identifying unexpected objects and tendency towards intrusive thought patterns. This design should minimise the influence of top-down factors such as familiarity, allowing us to focus more on stimulus-driven influences. We demonstrated that expert drivers performed better than non-expert, novice and young-competent drivers in tasks designed to reflect on-task performance such as continuous performance and task-intrusive-thoughts. However, in visual search, noticing the unexpected object in Inattentional Blindness (IB), and multiple object tracking in IB, expert drivers were the same as the two younger driver groups. The results suggest that – in driving at least – expertise is qualitatively different from experience, and driving expertise may be partially derived from superior skill in underlying core visuo-cognitive constructs. This finding is important for understanding driver training programs, but also in understanding the 'backward transference' of expertise to underlying cognitive-perceptual networks.